Magneto-rheological damper design characteristics for vehicle airbag replacement - Dhanaletchmi N.; Nagi F.H.; Ramasamy A.K. (Inderscience Publishers, 2023)
Accidents; Automobile air bags; Fuzzy logic; Proportional control systems; Two term control systems; airbag; Car crashes; damper; Magneto-rheological; Seat belt; Damping